The Clown, the Criminal, and the Dummy: Alternate Interpretations of Oppositional Behaviors - Brendaly Drayton (Adult Education Research Conference, 2014)
Drawing upon the narratives of three African American men who dropped out of school, the paper proposes that oppositional behaviors may be underpinned by self-protective strategies based upon perceived available options and that commonly held stereotypes can lead to the misinterpretation of actions.